2012
DOI: 10.1369/0022155412437218
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Disease-associated Prion Protein in the Optic Nerve and the Adrenal Gland of Cattle with Bovine Spongiform Encephalopathy by Using Highly Sensitive Immunolabeling Procedures

Abstract: A sensitive immunohistochemical procedure, the tyramide signal amplification (TSA) system, was applied to detect the localization of immunolabeled disease-associated prion protein (PrPSc) in cattle affected with bovine spongiform encephalopathy (BSE). In this procedure, immunolabeling could be visualized in the optic nerve and the adrenal medulla. In the optic nerve, the dual immunofluorescent technique showed that the granular PrPSc was occasionally detected in the astrocytes, microglia, and myelin sheath adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 48 publications
2
22
0
Order By: Relevance
“…In addition, granular PrP Sc was observed by dual immunofluorescence and found to be located at the periphery of axons, suggestive of an ad-axonal location in the white matter of the spinocerebellar tract and the olivocerebellar tract (Fig. 2E) [22]. Association of PrP Sc with either astrocytes or microglia [23] was not detected in the brainstem (data not shown), agreeing with other reports of atypical scrapie cases [3, 25].…”
supporting
confidence: 86%
See 1 more Smart Citation
“…In addition, granular PrP Sc was observed by dual immunofluorescence and found to be located at the periphery of axons, suggestive of an ad-axonal location in the white matter of the spinocerebellar tract and the olivocerebellar tract (Fig. 2E) [22]. Association of PrP Sc with either astrocytes or microglia [23] was not detected in the brainstem (data not shown), agreeing with other reports of atypical scrapie cases [3, 25].…”
supporting
confidence: 86%
“…The blotted membranes were probed with the monoclonal antibody (mAb) P4 (R-Biopharm, Darmstadt, Germany) according to a previously described method [23]. IHC for PrP Sc was performed using the mAb T1 [27] or F99/97.6.1 (VMRD, Pullman, WA, U.S.A.) as previously described [22,23,24]. Additionally, formalin-fixed and paraffin-embedded tissue sections were stained with an anti- Listeria monocytogenes (Lm) polyclonal antibody [1] and a secondary Alexa Fluor 546-conjugated antibody for dual immunofluorescence.…”
mentioning
confidence: 99%
“…Modifications using fluoresceinated tyramide result in marked reduction or ablation of background from endogenous biotin. 139,140,259,389 Immuno-Rolling Circle Amplification. Rolling circle amplification (RCA) increases the signal of the immunologic reaction without increasing the noise (background) that can occur with the tyramide amplification method.…”
Section: Avidin-biotin Methodsmentioning
confidence: 99%
“…Recent studies have demonstrated that ganglion cells from within the adrenal medulla are also likely to project ascending axons and may relay information from the adrenal medulla to the CNS [26], [27]. The nature of the immunolabelling pattern of the adrenal medulla of BSE infected cattle [28] and scrapie infected sheep [29] indicate that fine preganglionic sympathetic nerve processes may accumulate PrP d . There remain two possible routes by which the adrenal medulla may become infected following natural infection.…”
Section: Introductionmentioning
confidence: 99%